Breaking Empirical Deadlocks in the Study of Partisanship: An Overview of Experimental Research Strategies - Green, Donald P. (2013)
The vast literature on party identification has gradually become bogged down by disputes about how to interpret observational data. This paper proposes the use of experimental designs to shed light on the responsiveness of party identification to short term forces such as retrospective performance evaluations. Examples of recent field experiments are used to illustrate two types of experimental designs and the assumptions on which they rest.